Research in the Central Part of Severynivka Hillfort (Quadrats F80, F90, G71, G81) - Shelekhan, Oleksandr; Lifantii, Oksana; Boltryk, Yuriy; Ignaczak, Marcin (Baltic-Pontic Studies, 2016)
The article deals with excavations in the central part of Severynivka hillfort. In the mentioned area there was found and studied a part of the large multi-layered complex, which is considered as the remains of probable public worship structure. In the complex filling there were revealed numerous finds of wares, including a number of complete tableware and miniature forms, tools, jewelry and weapons. Also there were traced the tracks of rites administering that is recorded by the physical layout of objects in the complex and a female jaw find.